PENINGKATAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI STORYTELLING CERITA RAKYAT KEPADA MAHASISWA ALIYAH PONDOK PESANTREN DARUL MURSYIDI SIALOGO - Nursaima harahap (LPPM Universitas Timor, 2021)
Story telling is a way of learning that has been used since ancient times and has become a very important learning tool. The teacher tells a story or literary work through story telling and the students do too. Morrow explained that story telling is an activity is fun and stimulates the imagination of students. The reason of teams took this theme was very well known in the North Sumatera region, especially the Mandailing Natal community and story telling was a way of learning that has been used since ancient times and has become a very important learning tool. The teacher conveys a story or literacy work through storytelling and the students do likewise. In addition to make this learning not monotonous, the teacher making groping into several groups then teacher shares English text which contains the story of Sampuraga to each group and tells the students to underline what they know the meaning of as many as 20 words in a period of 15 minutes and the teacher monitors students’ activities. After that, each group wrote down the vocabulary and meanings on the whiteboard in turn so that the students could understand the contents of the story about sampuraga.